Synergy of Adsorption and Photocatalytic Reduction for Efficient Removal of Cr(VI) with Polyvinylidene FluoridePolyvinyl Alcohol-FeC2O4/Bi2.15WO6 - Li, Da-Shuai (Langmuir : the ACS journal of surfaces and colloids, 2023)
Although the photocatalytic reduction of Cr(VI) to Cr(III) by traditional powder photocatalysts is a promising method, the difficulty and poor recovery of photocatalysts from water hinder their wide practical applications. Herein, we present that FeC2O4/Bi2.15WO6 (FeC2O4/BWO) composites were tightly bonded to modified polyvinylidene fluoride (PVDF) membranes by chemical grafting with the aid of polyvinyl alcohol (PVA) to form photocatalytic composite membranes (PVDFPVA-FeC2O4/BWO). The contact angle of PVDF@PVA-FeC2O4/BWO (0.06 wt % of FeC2O4/BWO) is 48.0°, which is much lower than that of the pure PVDF membrane (80.5°). Meanwhile, the permeate flux of 61.43 g m-2 h-1 and water flux of 250.60 L m-2 h-1 were observed for PVDF@PVA-FeC2O4/BWO composite membranes. The tensile strength of composite membranes reached 48.84 MPa, which was 9.8 times higher than that of PVDF membrane. It was found that the PVDF@PVA-FeC2O4/BWO membrane exhibited excellent photocatalytic Cr(VI) reduction performance under both simulated and real sunlight irradiation. The adsorption for Cr(VI) by PVDF@PVA-FeC2O4/BWO can reach 47.6% in the dark process within 30 min, and the removal percentage of Cr(VI) could reach 100% with a rate constant k value of 0.2651 min-1 after 10 min of light exposure, indicating a synergistic effect of adsorption and photoreduction for Cr(VI) removal by the composite membrane. The PVDF@PVA-FeC2O4/BWO membrane had good stability and reusability after seven consecutive cycles. Most importantly, the influences of foreign ions on Cr(VI) reduction were investigated to mimic real sewage, which revealed that no obvious adverse effects can be found with the presence of common foreign ions in sewage. The photocatalytic membrane material developed in this study provides a new idea for treating Cr(VI)-containing wastewater and has a more significant application prospect